N-(3-Oxododecanoyl) Homoserine Lactone Is a Generalizable Plasma Membrane Lipid-Ordered Domain Modifier - Ruan, Hefei; Zou, Chunlin; Xu, Yanni; Fang, Xiaohong; Xia, Tie; Shi, Yan (Frontiers in Physiology, 2022)
A mammalian plasma membrane is a structure on which several layers of complexity are built. The first order of complexity comes from the heterogeneity of lipid-ordered domains. Gangliosides in concert with cholesterol are preferentially packed on the outer leaflet and form lipid-ordered domains, commonly known as lipid rafts. The formation and dynamics of these domains impact nearly all membrane protein functions and are an intensely studied topic. However, tools suited for lipid domain alteration are extremely limited. Currently, methyl-β-cyclodextrin (MβCD) appears to be the most common way to disrupt lipid domains, which is believed to operate via cholesterol extraction. This significantly limits our ability in membrane biophysics research. Previously, we found that N-(3-oxo-dodecanoyl) homoserine lactone (3oc), a small signaling chemical produced by Pseudomonas aeruginosa, is highly efficient in altering lipid-ordered domains. In this study, 3oc was compared with MβCD in a series of biochemical, biophysical, and cell biological analyses. Per molarity, 3oc is more efficient than MβCD in domain alteration and appears to better retain membrane lipids after treatment. This finding will provide an essential reagent in membrane biophysics research.